Global burden of oesophageal and gastric cancer by histology and subsite in 2018. Issue 9 (30th June 2020) - Arnold, Melina; Ferlay, Jacques; van Berge Henegouwen, Mark I; Soerjomataram, Isabelle
Abstract : Objectives: To provide updated estimates of the global burden of oesophageal and gastric cancer by subsite and type. Methods: Using data from population-based cancer registries, proportions of oesophageal adenocarcinoma (OAC) and squamous cell carcinoma (OSCC) out of all oesophageal as well as cardia gastric cancer (CGC) and non-CGC (NCGC) out of all gastric cancer cases were computed by country, sex and age group. Proportions were subsequently applied to the estimated numbers of oesophageal and gastric cancer cases from GLOBOCAN 2018. Age-standardised incidence rates (ASR) were calculated. Results: In 2018, there were an estimated 572 000 new cases of oesophageal cancer worldwide, 85 000 OACs (ASR 0.9 per 100 000, both sexes combined) and 482 000 OSCCs (ASR 5.3). Out of 1.03 million gastric cancers, there were an estimated 181 000 cases of CGC (ASR 2.0) and 853 000 cases of NCGC (ASR 9.2). While the highest incidence rates of OSCC, CGC and NCGC were observed in Eastern Asia (ASRs 11.1, 4.4 and 17.9, respectively), rates of OAC were highest in Northern Europe (ASR 3.5). While globally OSCC and NCGC remain the most common types of oesophageal and gastric cancer, respectively, rates of OAC exceed those of OSCC in an increasing number of high-income countries. Conclusions: These updated estimates of the global burden of oesophageal and gastric cancer by subtype and site suggest an ongoing transition in epidemiological patterns. This work will serve as a cornerstone for policy-making and will aid in developing appropriate cancer control strategies.